Pengembangan Media Pembelajaran Biologi Berbasis Ulead Video Studio 11 - Ari Yanti Yanti (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2018)
This study aims to develop Ulead Studio Studio 11 based biology learning media on digestion system material and to know the validity, practicality and effectivity of instructional videos based on validation and field trials. This research is Research and Development (R & D) type. The development model used the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. To obtain the feasibility of learning video, used three tests analysis that are, validity tests, practicality test, and effectiveness test. Trial conducted at SMA YPWI Tanjung Pinang and SMA Negeri 11 Kota Jambi. The result of this study is a decent learning video based on the results of the assessment of design experts, material experts, language of 86.66%, 9.66%, 90% so that entered in the category is very valid. Then the results of the analysis of the teacher's practicality sheet stated that the developed media was included in the